2013
DOI: 10.1371/journal.pone.0074313
|View full text |Cite
|
Sign up to set email alerts
|

EMMPRIN Promotes Angiogenesis, Proliferation, Invasion and Resistance to Sunitinib in Renal Cell Carcinoma, and Its Level Predicts Patient Outcome

Abstract: PurposeExtracellular matrix metalloproteinase inducer (EMMPRIN) has been reported to play crucial roles, including in angiogenesis, in several carcinomas. However, the correlation between EMMPRIN levels and angiogenesis expression profile has not been reported, and the role of EMMPRIN in renal cell carcinoma (RCC) is unclear. In the present study, we evaluated the association of EMMPRIN with angiogenesis, its value in prognosis, and its roles in RCC.Experimental DesignEMMPRIN expression was examined in 50 RCC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 45 publications
0
37
0
2
Order By: Relevance
“…Minardi et al [51] showed that VEGF expression was correlated with distant metastasis-free survival (DMFS) and OS in mRCC patients, but showed no association with regard to sunitinib treatment [51]. In a set of 50 Japanese RCC patients, Sato et al [52] investigated the Extracellular Matrix MetalloPRoteinase Inducer (EMMPRIN), a cell-surface glycoprotein that belongs to the immunoglobulin superfamily encoded by a gene localized to 19p13.3. High expression of EMMPRIN was seen for sunitinib-treated patients and sunitinib-resistant cells [52].…”
Section: Protein Expression and Immunoexpression In Sunitinib Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Minardi et al [51] showed that VEGF expression was correlated with distant metastasis-free survival (DMFS) and OS in mRCC patients, but showed no association with regard to sunitinib treatment [51]. In a set of 50 Japanese RCC patients, Sato et al [52] investigated the Extracellular Matrix MetalloPRoteinase Inducer (EMMPRIN), a cell-surface glycoprotein that belongs to the immunoglobulin superfamily encoded by a gene localized to 19p13.3. High expression of EMMPRIN was seen for sunitinib-treated patients and sunitinib-resistant cells [52].…”
Section: Protein Expression and Immunoexpression In Sunitinib Treatmentmentioning
confidence: 99%
“…In a set of 50 Japanese RCC patients, Sato et al [52] investigated the Extracellular Matrix MetalloPRoteinase Inducer (EMMPRIN), a cell-surface glycoprotein that belongs to the immunoglobulin superfamily encoded by a gene localized to 19p13.3. High expression of EMMPRIN was seen for sunitinib-treated patients and sunitinib-resistant cells [52]. In the above-mentioned study of Motzer et al [33], baseline levels of angiopoietin-2 and matrix metalloproteinase were associated with tumor response, and HIF-1α expression was associated with PFS [33].…”
Section: Protein Expression and Immunoexpression In Sunitinib Treatmentmentioning
confidence: 99%
“…Sato et al [9] investigated the role of EMMPRIN in resistance to sunitinib, showing in his study that the use of sunitinib may lead to EMMPRIN overexpression, a phenomenon related to tumor growth and angiogenesis activity.…”
Section: Resistancementioning
confidence: 99%
“…Moreover, in most cases, this therapeutic option represents no definitive cure. Even in cases that initially respond well to sunitinib, tumor regrowth occurs owing to chemoresistance [9].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have focused on its potential biological functions in malignant tumors and have revealed that upregulation of CD147 may contribute to carcinogenesis and tumor cell migration in several cancer types, such as colorectal adenocarcinoma (10)(11)(12) and head and neck squamous cell carcinoma (13). Sato et al (14) further reported that CD147 expression levels are predictors of the outcome for renal cell carcinoma patients. A mechanistic assessment by Iacono et al (15) suggested that CD147 elevated the expression levels of various metalloproteinases to promote carcinogenesis, angiogenesis and metastasis (16).…”
Section: Introductionmentioning
confidence: 99%